Influence of hepatitis C virus infection and high virus serum load on biliary complications in liver transplantation. Issue 3 (15th March 2013) - Horster, S.; Bäuerlein, F.J.B.; Mandel, P.; Raziorrouh, B.; Hopf, C.; Stemmler, H.J.; Guba, M.; Angele, M.; Stangl, M.; Rentsch, M.; Frey, L.; Kaspar, M.; et al.
Abstract: Background: Biliary complications (BCs) and recurrent hepatitis C virus (HCV) infection are among the major causes of morbidity and graft loss following liver transplantation. The influence of HCV on BCs has not been definitely clarified. Patients and methods: We performed a retrospective cohort study to analyze risk factors and outcome of post orthotopic liver transplantation (OLT) BCs in 352 liver transplant recipients over 12 years in Munich, Germany ( n = 84 with HCV; living donor and re‐OLT were excluded). BCs diagnosed with imaging techniques and abnormal liver enzyme pattern, requiring an intervention, were considered. Results: In a multivariate analysis, HCV serostatus and a high pre‐and post‐surgery HCV RNA serum load were independent risk factors for anastomotic strictures. HCV positivity and BCs alone did not alter graft loss. HCV‐positive patients with BCs, however, had a significantly worse graft outcome ( P = 0.02). Non‐anastomotic strictures, bile leaks, and the number of interventions needed to treat bile leaks led to worse graft outcome in all patients. Conclusion: HCV positivity and a high HCV RNA serum load were risk factors for anastomotic strictures. BCs and HCV had an additive effect on graft loss.